2015
DOI: 10.1002/2014jb011814
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the oceanic lithosphere inferred from Po/So waves traveling in the Philippine Sea Plate

Abstract: Po/So waves are characterized by their high-frequency content and long-duration travel over great distances (up to 3000km) through the oceanic lithosphere. Po/So waves are developed by the multiple forward scattering of P and S waves due to small-scale stochastic random heterogeneities. To study the nature of these heterogeneities, Po/So waves are analyzed in the Philippine Sea Plate, which consists of three regions with different lithospheric ages. In the Philippine Sea Plate, Po/So waves propagate in the you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 24 publications
5
31
1
Order By: Relevance
“…amplitude of stochastic variation 2%). The work of Shito et al [2013] demonstrates that the same model of heterogeneity is applicable in the old oceanic lithosphere of the NW Pacific and in the subducting Pacific plate beneath Japan A similar uniform distribution of heterogeneity (amplitude 2%) has been used by Shito et al [2015] in a study of Po and So propagation in the much younger lithosphere of the Philippine Sea plate. They note systematic thickening of the lithosphere with increasing age, and favor an even longer horizontal correlation length than for the northwest Pacific.…”
Section: Seismological Heterogeneitymentioning
confidence: 81%
See 1 more Smart Citation
“…amplitude of stochastic variation 2%). The work of Shito et al [2013] demonstrates that the same model of heterogeneity is applicable in the old oceanic lithosphere of the NW Pacific and in the subducting Pacific plate beneath Japan A similar uniform distribution of heterogeneity (amplitude 2%) has been used by Shito et al [2015] in a study of Po and So propagation in the much younger lithosphere of the Philippine Sea plate. They note systematic thickening of the lithosphere with increasing age, and favor an even longer horizontal correlation length than for the northwest Pacific.…”
Section: Seismological Heterogeneitymentioning
confidence: 81%
“…A similar uniform distribution of heterogeneity (amplitude 2%) has been used by Shito et al . [] in a study of Po and So propagation in the much younger lithosphere of the Philippine Sea plate. They note systematic thickening of the lithosphere with increasing age, and favor an even longer horizontal correlation length than for the northwest Pacific.…”
Section: Seismological Heterogeneitymentioning
confidence: 99%
“…However, we detected mantle reflectors beneath the normal ocean basin, where crustal thickening due to intraplate volcanism does not occur. The other interpretation is that the mantle reflectors represent quasi-laminate heterogeneities in the lithospheric mantle; such heterogeneities have been identified previously by analyzing Po and So waves, which are characterized by their high-frequency (> 2.5 Hz) content and their propagation for great distances in the oceanic lithosphere, with quasi-laminate features with a horizontal correlation length of around 10 km and a vertical correlation length of 0.5 km and a velocity perturbation of a few percent (e.g., Shito et al 2015;Kennett and Furumura 2015). These heterogeneities are considered to have formed continuously in the oceanic lithosphere from the time of its formation at a mid-ocean ridge via the solidification of melts attached to the bottom of the lithosphere (Shito et al 2015).…”
Section: Heterogeneity In the Oceanic Lithospherementioning
confidence: 96%
“…The other interpretation is that the mantle reflectors represent quasi-laminate heterogeneities in the lithospheric mantle; such heterogeneities have been identified previously by analyzing Po and So waves, which are characterized by their high-frequency (> 2.5 Hz) content and their propagation for great distances in the oceanic lithosphere, with quasi-laminate features with a horizontal correlation length of around 10 km and a vertical correlation length of 0.5 km and a velocity perturbation of a few percent (e.g., Shito et al 2015;Kennett and Furumura 2015). These heterogeneities are considered to have formed continuously in the oceanic lithosphere from the time of its formation at a mid-ocean ridge via the solidification of melts attached to the bottom of the lithosphere (Shito et al 2015). In a previous active-source seismic survey conducted southeast of the Shatsky Rise, we observed such frozen melts at depths of 37-59 km (Ohira et al 2017b), but based on that study we were unable to determine whether such heterogeneities are ubiquitous in the lithosphere or restricted to specific regions.…”
Section: Heterogeneity In the Oceanic Lithospherementioning
confidence: 96%
“…When P and S waves are excited by an earthquake occurring within the subducting slab, Po and So waves are developed from the multiple scatterings of the P and S waves owing to small-scale stochastic random heterogeneities in the oceanic mantle (Shito et al 2013). These waves propagate over distances up to 3000 km and often manifest long-duration, high-frequency (> 2 Hz) recordings in the seafloor observation (Kennett and Furumura, 2013;Shito et al 2013Shito et al , 2015. This study used Po waves observed in the northwestern part of the Pacific Plate ( Fig.…”
Section: Introductionmentioning
confidence: 99%